Husbands' Feelings Toward Their Wives’ Breastfeeding in Public Places in Yogyakarta - Santahana Febrianti; Maria Irma C. Bustamante (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: Breastfeeding has so many benefits for both mother and child. In Indonesia, there are only 42% of children who were exclusively breastfed. There were still many husbands who do not know about the importance and barriers of breastfeeding, especially in public spheres and how they took part in it. The study aimed to explore the husbands’ feeling towards their wives’ breastfeeding in public places in Yogyakarta. Methods: The study conducted the qualitative exploratory design. The terms of exploratory was related with investigation husband’s feeling through in-depth interview. There were 7 participants who were interviewed selected through purposive sampling and analyzed using thematic analysis. Results: This study collated 4 major themes based on the responses. These were Feelings based on religion, Feelings based on socio-cultural influence, Feelings based on personal views and Feelings related to health reason. A brochure was created by providing guidelines for husband on his role to support wives’ breastfeeding in public places. Conclusion: Increasing public awareness needs to build breastfeeding-friendly facilities in public places in accordance the laws and regulations. The role of nurse as an educator needs to promote exclusive breastfeeding and contributes to provide accurate information to the family.